Induced eddy currents characteristics of coal gangue-based functional concrete in compression process - Meng XIAO; Feng JU; Zequan HE; Pai NING; Tengfei WANG; Dong WANG (Meitan kexue jishu, 2025)
Coal gangue-based cemented structures （CGCS） have been widely used in underground engineering. Due to the complex environment and limited space, there is still no effective method to monitor structural health in under-ground engineering. Adding conductive additives in coal gangue-based cemented materials, its conductive proper-ties can be enhanced. The changes of electrical parameters during loading can be detected by eddy current testing method, and then the stress state of CGCS can be calculated. This method can overcome the drawbacks about installation and maintenance induced by embedded sensor. The eddy current testing platform based on STM32 microcontroller was designed, .and the CGCS specimens containing steel fibers were prepared. The mechanical and eddy current inducting tests were conducted, and the signal changes of specimens with different steel fiber content during uniaxial compress, cyclic loading were analyzed. The results show that the change in stages of eddy current induction signal has a strong consistency with that of stress-strain curves. The fractional changes in resistivity (FCR) of specimens under uniaxial compressive loading can be divided into 3 stages, including initial constancy, rapid decline, and then slow decline. These 3 stages correspond to the compaction, elastic and after-peak stages in stress-strain curves. In cyclic loading test, the voltage difference changes of specimens with 0.8% and 1.2% steel fiber contents were consistent to the cyclic compressive loading, and the cyclic changes of “steel fibers contact – increase of conductive paths – steel fibers separation – decrease of conductive paths” were shown. Higher steel fibers content cannot further improve the sensitivity of the voltage difference to cyclic loading. With the SF content of specimens in-creasing from 0.4% to 2.0%, the gauge factor increases first and then decreases, and the linearity of eddy current induction signal decreases linearly. The CGCS specimens with 0.8% SF content have highest gangue factor during uniaxial and cyclic compressive loading test.